Cu(OTf)(2) or Et3N-catalyzed three-component condensation of aldehydes, amines and cyanides: a high yielding synthesis of alpha-aminonitriles - Paraskar, Abhimanyu S.; Sudalai, Arumugam (Tetrahedron Letters, 2006)
Copper(II) triflate or Et3N have been found to catalyze, under ambient conditions, the addition of a cyanide anion, such as trimethylsilyl cyanide or acetone cyanohydrin, onto in situ generated imines, furnishing alpha-aminonitriles in excellent yields. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: aldehydes; aminonitriles; multicomponent reactions; organocatalyst; Strecker reaction

Organocatalytic activation of TMSCN by basic ammonium salts for efficient cyanation of aldehydes and imines - Raj, I. Victor Paul; Suryavanshi, Gurunath; Sudalai, A. (Tetrahedron Letters, 2007)
Basic ammonium salts act as highly effective catalysts for the cyanosilylation of aldehydes and in Strecker-type aminonitrile synthesis using TMSCN as cyanide source at 25 degrees C under extremely mild conditions, affording very good to excellent yields of silylated cyanohydrins and alpha-aminonitriles. (C) 2007 Published by Elsevier Ltd.
Keywords: aldehydes; aminonitriles; cyanohydrin; cyanosilylation; multicomponent reactions; TMSCN

Practical and highly efficient protocol for multicomponent synthesis of beta-phosphonomalononitriles and 2-amino-4H-chromen-4-yl phosphonates using diethylamine as a novel organocatalyst - Kulkarni, M. A.; Pandurangi, V. R.; Desai, Uday V.; Wadgaonkar, P. P. (Comptes Rendus Chimie, 2012)
Diethylamine has been demonstrated for the first time to be a highly efficient organocatalyst in the solvent-free synthesis of beta-phosphonomalononitriles by a three component condensation of aldehyde, malononitrile and dialkyl phosphite at ambient temperature. The applicability of the same catalyst in the synthesis of diethyl (2-amino-3-cyano-chromene-4-yl) phosphonic acid esters has also been described. (c) 2012 Published by Elsevier Masson SAS on behalf of Academie des sciences.
Keywords: 2-amino-4H-chromenes; beta-phosphonomalononitriles; diethylamine; multicomponent reactions; organocatalyst; Phospha-Michael reaction

Diethylamine: a smart organocatalyst in eco-safe and diastereoselective synthesis of medicinally privileged 2-amino-4H-chromenes at ambient temperature - Kulkarni, Makarand A.; Pandit, Kapil S.; Desai, Uday V.; Lad, Uday P.; Wadgaonkar, Prakash P. (Comptes Rendus Chimie, 2013)
Diethylamine has been demonstrated to be an efficient organocatalyst in the diastereoselective synthesis of Bcl-2 protein antagonist (HA-14-1) and of its structural analogues by one-pot condensation between salicylaldehyde and three different C-H acids, viz, ethyl cyanoacetate, phenylsulfonyl acetonitrile, and malononitrile. Easy commercial availability of the catalyst at extremely low cost and avoidance of conventional work-up as well as purification procedures qualifies this scalable protocol for a ``near-ideal synthesis''. (c) 2013 Academie des sciences. Published by Elsevier Masson SAS. All rights reserved.
Keywords: 2-amino-4H-chromenes; Active methylene compounds (C-H acids); diethylamine; multicomponent reactions; organocatalyst

Silicon-induced general, mild, and efficient one-pot, three-component synthesis of amidoalkyl naphthol libraries - Salama, Tarek A. (Synlett, 2013)
A general mild and efficient protocol for the synthesis of amidoalkyl naphthol libraries was achieved utilizing tetrachlorosilane and zinc chloride in dichloromethane at ambient temperature via a one-pot, three-component condensation of various aldehydes, nitriles (amides), and beta-naphthol.
Keywords: amidoalkyl naphthols; combinatorial synthesis; multicomponent reactions; Ritter reaction; tetrachlorosilane

Simple, economical, and environmentally benign protocol for the synthesis of 2-amino-3,5-dicarbonitrile-6-sulfanylpyridines at ambient temperature - Desai, Uday V.; Kulkarni, Makarand A.; Pandit, Kapil S.; Kulkarni, Aparna M.; Wadgaonkar, Prakash P. (Green Chemistry Letters and Reviews, 2014)
A simple, economical, and environmentally benign protocol has been described for one-pot synthesis of medicinally privileged 2-amino-3,5-dicarbonitrile-6-sulfanylpyridines by three-component condensation between aldehyde, malononitrile, and thiol using diethylamine as a catalyst. Ambient temperature and avoidance of conventional work-up as well as purification procedure qualify this cost-effective protocol for ``green synthesis.''
Keywords: 5-dicarbonitriles; diethylamine; green chemistry; multicomponent reactions; organocatalyst; pyridine-3

[DBUH][OAc]-catalyzed domino synthesis of novel benzimidazole incorporated 3,5-Bis (Arylidene)-4-piperidones as potential antitubercular agents - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Nagargoje, Amol A.; Sarkar, Dhiman; Khedkar, Vijay M.; Shingate, Bapurao B. (Polycyclic Aromatic Compounds, 2022)
A series of new benzimidazole incorporated 3,5-bis (arylidene)-4-piperidones were synthesized by using aryl aldehydes, piperidinone, 2-(chloromethyl)-benzimidazole and DBU acetate [DBUH][OAc] act as a catalyst under solvent free condition in excellent yields. The synthesized compounds were screened for their in vitro antimycobacterial activity against M. tuberculosis H37Ra (MTB) and M. bovis BCG strains. The compounds 4a, 4b, 4e, 4i, 4k and 4l are highly potent against both the strains. Most of the active compounds are non-cytotoxic against MCF-7, A549, HCT 116 and THP-1 cell lines. Furthermore, a molecular docking study of these compounds was carried out to investigate their binding pattern with the target, active site of mycobacterial enoyl-acyl carrier protein reductase (Inh A). Therefore, these compounds can be subjected for further optimization and drug development which could give promising chemical leads for treatment of TB.
Keywords: Antitubercular activity; curcumin; Cytotoxicity; Ionic liquid; multicomponent reactions

[DBUH][HSO4]-catalyzed solvent-free synthesis of 1,5-benzodiazepine derivatives: bioevaluation and in silico molecular docking study - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Nagargoje, Amol A.; Sarkar, Dhiman; Khedkar, Vijay M.; Shingate, Bapurao B. (Current Organic Chemistry, 2025)
Here, we report the solvent-free one-pot multicomponent synthesis of 4-substituted-1,5-benzodiazepine derivatives from O-phenylenediamine, aromatic aldehydes, and dimedone using [DBUH][HSO4] as a catalyst in excellent yields. This process was carried out in search of a reusable, easily accessible, affordable, and efficient catalyst. 1,5-Benzodiazepines demonstrate a new family of good inhibitors with potent anti-mycobacterial properties. The most promising compounds in the present series are 4c, 4i, and 4l which showed excellent activity and inhibited the growth of both MTB H37Ra and M. bovis BCG strains with lower MICs. The most active compounds were further studied for their cytotoxicity against cell lines MCF-7, A549, HCT116, and THP-1 by MTT assays and the compounds were found to be non-toxic. The fact that none of these compounds work against either Gram-positive or Gram-negative bacteria suggests that they are only effective against MTB. The in silico docking of the molecules against mycobacterial enoyl reductase, InhA enzyme could provide well-clustered solutions and have given valuable insights into the thermodynamic elements governing the binding affinities. The findings of this investigation unmistakably point to the discovery of extremely specific and selective MTB inhibitors, which can now be investigated further in search of possible anti-tubercular drugs.
Keywords: 1; 5-benzodiazepine; Antitubercular activity; Molecular docking; multicomponent reactions; [DBUH][HSO4]

Ketenimine multicomponent strategy for multifaceted amidine functionalization of peptides on the solid phase - Bodake, Supriya Mahadev; Marelli, Udaya Kiran (Angewandte Chemie-International Edition, 2025)
The amidine group and its derivatives serve as proteolytically stable bioisosteres of the peptide bond, and their selective incorporation into peptides attributes significant chemical and biological features. This study introduces an efficient synthesis of amidine-containing peptides by a copper-catalyzed, solid-phase-compatible multicomponent reaction (MCR), leveraging ketenimine intermediates that are generated in situ. Through the reaction of sulfonyl azides with terminal alkynes and a wide variety of amines, we establish the robust on-resin synthesis of delta/epsilon-amidine amino acids, arginine isologues, fluorescently labeled peptides, drug-peptide hybrids, and PEGylated derivatives. This strategy notably supports a wide range of peptide modifications, including side chain alteration, amine functionalization, and peptide macrocyclization through both backbone and side chain groups, as well as incorporating aromatic scaffolds into the peptide backbone. The methodology demonstrates broad substrate tolerance, compatibility with peptide chemistry protocols, and access to complex motifs, including pharmacophores and imaging tags, all within a single reaction platform. Our results underscore the synthetic versatility and functional applicability of ketenimine-based MCRs for advanced peptide modification, expanding the chemical space of peptide medicinal chemistry and therapeutics.
Keywords: Amidines; multicomponent reactions; peptide modification; Peptide-small molecule hybrids; Solid phase peptide synthesis